Short- and long-term assessment of PAH, PCB, and metal contamination in the Belgian part of the North Sea. (January 2023) - Vanavermaete, David; Hostens, Kris; Le, Hong Minh; Lessuise, Amélie; Ruttens, Ann; Waegeneers, Nadia; De Witte, Bavo
Abstract: Dredging activities can result in the relocation of contaminants such as polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and metals from shipping channels, harbours, and ports into the marine environment where these components may exert a negative effect on the marine ecosystem. In this work, contamination associated with dredging is evaluated at and around dredged spoil disposal sites in the Belgian part of the North Sea, taking into account spatial as well as temporal variation. A homogeneous dispersion of the different contaminants was observed at the different sites. However, the contamination pattern was different for disposal sites that were linked with commercial ports, resulting in significantly higher PAH and PCB concentrations. When comparing concentrations with environmental assessment criteria, contamination of PAHs does not exceed these criteria in the Belgian Part of the North Sea, and for PCBs, only CB118 reveals a concerningly high concentration that exceeds the environmental assessment criteria. This is in contrast with metals where the contamination of As, Cr, Ni, and Zn exceeded the environmental limit values both at dredged spoil disposal sites and reference locations. Graphical abstract: Image 1 Highlights: Links between contamination at ports and the marine environment reveal the impact of dredging. Dredged spoil disposal sites tend to spread over a larger area, rendering the control-impact design of monitoring programs difficult. Several metals exceeds the environmental assessment criteria imposing a risk for the marine environment.